Effects of brown algal phlorotannins and ascorbic acid on the physiochemical properties of minced fish (Pagrosomus major) during freeze–thaw cycles. (8th January 2017) - Wang, Tiantian; Li, Zhenxing; Mi, Nasha; Yuan, Fangzhou; Zou, Long; Lin, Hong; Pavase, Tushar
Summary: The quality loss in fish during freeze–thaw cycles is considered one of the major issues caused mainly by temperature fluctuations during cold storage. The present work is aimed to illustrate the effects of brown algal phlorotannins (BAP) and ascorbic acid (AA) on physiochemical properties of minced snapper muscle through different freeze–thaw cycles. Both AA and BAP could retard lipid and protein oxidation, respectively, and synergistically. The Ca 2+ ‐ATPase activity can be protected with the addition of antioxidants. The addition of 0.1% (w/w) AP showed 22.6% higher activity as compared with other groups especially during three freeze–thaw cycles. Cooking loss was efficiently inhibited and 0.1% AA + 0.3% BAP group showed 25.5% lower than control. Antioxidant is also helpful to maintain gel‐forming ability of minced snapper and 0.1% AA + 0.1% BAP group showed the best. These results revealed that both AA and BAP could prevent minced fish by inhibiting the protein denaturation during freeze–thaw cycles. Abstract : Effects of antioxidations on the physiochemical properties of minced fish (Pagrosomus major) during freeze–thaw cycles.